CINNAMON OIL-LOADED MgO/CuO NANOCOMPOSITE: A POTENTIAL ANTIMICROBIAL AGENT AGAINST MULTI DRUG RESISTANT BACTERIA (Journal of Medical & Health Sciences Review, 2025)
Addressing wound infections caused by both gram-positive and gram-negative bacteria, a critical public health issue exacerbated by rising antibiotic resistance, necessitates innovative treatments. Essential oils (EOs) and biologically synthesized nanocomposites are emerging as promising, natural, and nanotechnological alternatives to synthetic antibiotics. Essential oils provide broad-spectrum antimicrobial effects through their bioactive compounds, while nanocomposites enhance drug delivery, improve bioavailability, and combat resistance by targeting pathogens more effectively. This study was conducted to evaluate the antibacterial activity of an Essential Oil-loaded MgO/CuO nanocomposite against clinical isolates of gram-positive Staphylococcus aureus and gram-negative Escherichia coli obtained from wound infections. The Essential Oil-loaded MgO/CuO nanocomposite was prepared using a previously established protocol. Its antibacterial efficacy was assessed dose-dependently using the agar well diffusion method to determine zones of inhibition and the broth dilution method to establish the Minimum Inhibitory Concentration (MIC). Data analysis was performed using GraphPad Prism. The nanocomposite demonstrated significant dose-dependent antibacterial activity. Notably, MRSA exhibited a large zone of inhibition (15 × 17 mm) at a 100 μL concentration, and E. coli showed an even larger zone (20 × 22 mm) at the same concentration. MIC and Colony Forming Unit (CFU) analysis confirmed a complete growth inhibition of both E. coli and MRSA at a very low concentration of 0.2 μL/mL, validating the potent antibacterial effect of the cinnamon oil-loaded CuO/MgO nanocomposite against multi-drug resistant (MDR) strains isolated from wound infections. In conclusion, this research highlights the potent antibacterial activity of the Essential Oil-loaded MgO/CuO nanocomposite against both the Gram-positive Staphylococcus aureus and the Gram-negative E. coli. These results suggest a strong potential for this nanocomposite as an effective, sustainable alternative to conventional antibiotics for combating wound infections and addressing the challenge of antibiotic resistance.